Active and passive exposure to tobacco and e-cigarettes during pregnancy - Schilling, Laura; Spallek, Jacob; Maul, Holger; Tallarek, Marie; Schneider, Sven (Maternal and child health journal, 2021)
Active and passive exposure to tobacco cigarettes during pregnancy is associated with multiple negative health outcomes for the fetus. In addition, exposure to e-cigarettes has been progressively discussed as a new threat to fetal health. Until now, there has been a lack of studies examining active and passive exposure to tobacco and e-cigarettes among pregnant women. The objective of our current STudy on E-cigarettes and Pregnancy (STEP) was to advance and complement the current knowledge regarding active and passive exposure to tobacco and e-cigarettes before pregnancy and during early and late pregnancy.